Multicenter clinical experience of real life Dalbavancin use in gram-positive infections. (April 2019) - Wunsch, S.; Krause, R.; Valentin, T.; Prattes, J.; Janata, O.; Lenger, A.; Bellmann-Weiler, R.; Weiss, G.; Zollner-Schwetz, I.
Highlights: In a multicenter, retrospective study 101 patients were treated with dalbavancin. Infections treated were endocarditis, prosthetic joint infections, osteomyelitis and skin and soft tissue infections. Clinical success rate was 89%. Tolerability and safety were excellent. Abstract: Dalbavancin, a lipoglycopeptide with prolonged half-life approved for the treatment of acute bacterial skin and soft tissue infections, can be used for the treatment of infections caused by gram-positive bacteria requiring long term treatment such as endocarditis, prosthetic joint infections (PJI) or osteomyelitis. Clinical data are limited in these settings. Objectives: To evaluate indications, safety, tolerability and long-term outcomes of dalbavancin-treated patients. Patients and methods Our multicenter, retrospective study includes patients who received dalbavancin in Austria from September 2016 to March 2018. 90-day outcomes and tolerability were determined. Results: A total of 101 patients were included in 3 centers (57% male, median age 65 years). The treated infections were PJI (31%), osteomyelitis (29%), endocarditis (25%) and acute bacterial skin and soft tissue infections (12%). Concomitant use of other antimicrobial substances was common (63%). The mean total cumulative dose of dalbavancin was 3, 357 mg (±2, 283 mg). Clinical success rate was 89%. Side effects occurred in 3/101 patients. Conclusion: In this real-life study dalbavancin was primarily used in off-label indications for treatment of PJI, osteomyelitis and endocarditis. Success rate was high (89%), tolerability and safety were excellent in this setting. Dalbavancin may therefore be used in these off-label indications as alternative treatment approach.